Snapshots - Magris, Claudio (Yale University Press, 2019)
A collection of brief, but intimate meditations on life and culture ranging from controversial matters to private moments The internationally acclaimed author Claudio Magris offers a collection of brief "snapshots" reflecting on life and culture from 1999 to 2013 through his very personal lens. Some pieces portray private, intimate moments, while others offer views on public, sometimes controversial matters; the tone is sometimes serious, sometimes humorous, sometimes ironic, but always engaging. The panoramic nature of the vignettes is broad in scope, encompassing a variety of subjects rendered in quick, decisive brushstrokes. It is a little like leafing through a photo album of our times and our society while a learned companion seated beside us offers a perceptive running commentary. Magris's wit--at times pungent, at times self deprecating, always keen--is refreshingly affable. A continuing adventure by the author who has reinvented "travel literature."